RESEARCH WRITING ABILITY OF SENIOR HIGH SCHOOL STUDENTS AS PERCEIVED BY TEACHERS OF SAMPLED SCHOOLS IN QUEZON CITY - Paurillo, Precy M (PEOPLE: International Journal of Social Sciences, 2019)
Research paper writing continues to be an uninteresting topic for many students. They may not have realized its significance in their relevant discipline and target workplaces especially now that the global context requires a productive research culture that can work along with the newest trends in education. The study shares an objective with The Tarlac State University when it set its goal during the International Research Conference (2017), which is to give avenues for faculty and student researchers to disseminate cutting edge research outputs in a wide range of disciplines while enabling them to build mutually beneficial partnerships with other nations and institutions. This descriptive study was conducted on all the Research teachers of sampled schools in Quezon City. Data were collected by a valid and reliable questionnaire. In total, 93 percent of students reported to be lacking motivation in research writing and the minimum score was found for interest in writing. On the other hand, 100 percent of students noted employing varied motivational activities in research writing as an answer to these challenges. This makes the role of the teacher in the explicit and motivating discussion of research writing through fun tasks in the classroom becomes crucial.